2005
DOI: 10.1007/s00192-005-1370-x
|View full text |Cite
|
Sign up to set email alerts
|

Stoller afferent nerve stimulation in woman with therapy resistant over active bladder; a 1-year follow up

Abstract: SANS treatment has a short-term positive effect in patients with resistant overactive bladder. However, it was also established that efficacy was maintained at 1 year in only 23% of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Several studies have been published evaluating the effects of PTNS on OAB [13-19]. According to these studies, the overall percentage of patients classified as “successfully treated” was 54.5-79.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been published evaluating the effects of PTNS on OAB [13-19]. According to these studies, the overall percentage of patients classified as “successfully treated” was 54.5-79.5%.…”
Section: Resultsmentioning
confidence: 99%
“…This observation explains the carryover effect following a cycle of stimulation, in which patients report an extended clinical effect after initial treatment for a variable period of time. However, clinical efficacy was only maintained for longer than one year of follow-up in less than 22% of participants [13]. In fact, it has been shown that over a oneyear period at least two, 12-week cycles are recommended to ensure sustained clinical effect for three months, on average [14].…”
Section: Commentsmentioning
confidence: 98%
“…The responders with positive response of PTNS were also shown in several studies from 2005 to 2006, ranging from 37.3% to 81.8%. [27][28][29][30][31] The terms of responders were more than 50% reduction in symptoms including urgency, frequency, incontinence episodes, 27,29,30 complete recovery after treatment, 28 overall treatment response rate 31 and subjective feeling of improvement. 27 In an RCT by Finazzi Agrò et al 32 comparing PTNS and sham procedure, there were 75% and 0% patients with 50% reduction After its approval by FDA in 2007, PTNS showed considerable promise in the management of OAB.…”
Section: Efficacymentioning
confidence: 99%